Vibrato profesionalnih moških glasov - Varošanec-Škarić, Gordana (2006)
Fundamental frequency modulation was investigated on 3 male trained opera voices: famous older bass-baritone (80 years old) and two younger bass-baritones (23 and 21 years old). Voices were recorded in same conditions in the studio of the Department of Phonetics. On the basis of prolonged vocals during the perfomance of arias, vocalizations, songs and scales, narrow sonogram pitch analyses and pictures of periodic pitch changes were made. Vibrato rate, f0 middle values, f0 standard deviation, f0 range, jitter (%), shimmer (dB), HNR (dB) were also calculated. For the purpose of identifying so called high singing formant, LTAS was made for each singing voice on the basis of speech and singing. The sellected tone lasted long enough to measure the time beween two waves on the spectrogram picture. As the vibrato rate varies during the tone, i.e. near the end vibrato rate grows, the middle of the tone duration was taken into account. It has been found that vibrato rate is within the standard limits of good singing voice (for older voice 6 Hz:f0 just over 150 Hz, 5, 1 Hz:f0 165, 88 and descends approximatelly to rate between 4, 28 and 4, 65 HZ for some pitches ; for younger voices 5 Hz: f0 168, 82Hz, 198, 29 Hz) with variability depending on notes and beats. Nowadays, vibrato between 5 and 6 is aesthetically desirable. Singing vibrato is also cultivated treated vocal tremor, and specific aestetical tremor enriches the voice. Threfore, it is admirable how aesthetically preserved older voice is, although tremor has become noticeably unperiodic because it is harder to control it and it is not easy to sing with the exact vibrato. Vibrato can be more clearly seen in higher harmonics because the differences are summed up. On the other hand, low pitch harmonics merge together. When vibratos measured on different notes are compared, it is obvious that good vibrato is more constant in middle singing ranges of f0 pitches than in very low or very high f0. The complete constancy was not the case for every single singer, i.e. different rate depends on the vocal, pitch, interpretation – type of the song. Good cultivated vibrato contributes to the impression of voice richness that is acoustically evident in the wider spectral shape of singing formants and in greater number of harmonics in the sonogram.
Projekt MZOS
ENG